Results dissemination of registered clinical trials across Polish academic institutions: a cross-sectional analysis. Issue 1 (22nd January 2020) - Strzebonska, Karolina; Wasylewski, Mateusz T; Zaborowska, Lucja; Riedel, Nico; Wieschowski, Susanne; Strech, Daniel; Waligora, Marcin
Abstract : Objectives: To establish the rates of publication and reporting of results for interventional clinical trials across Polish academic medical centres (AMCs) completed between 2009 and 2013. We aim also to compare the publication and reporting success between adult and paediatric trials. Design: Cross-sectional study. Setting: AMCs in Poland. Participants: AMCs with interventional trials registered on ClinicalTrials.gov. Main outcome measure: Results reporting on ClinicalTrials.gov and publishing via journal publication. Results: We identified 305 interventional clinical trials registered on ClinicalTrials.gov, completed between 2009 and 2013 and affiliated with at least one AMC. Overall, 243 of the 305 trials (79.7%) had been published as articles or posted their summary results on ClinicalTrials.gov. Results were posted within a year of study completion and/or published within 2 years of study completion for 131 trials (43.0%). Dissemination by both posting and publishing results in a timely manner was achieved by four trials (1.3%). Conclusions: Our cross-sectional analysis revealed that Polish AMCs fail to meet the expectation for timely disseminating the findings of all interventional clinical trials. Delayed dissemination and non-dissemination of trial results negatively affects decisions in healthcare.